2017
DOI: 10.1308/rcsann.2016.0276
|View full text |Cite
|
Sign up to set email alerts
|

The construction and implementation of a clinical decision-making algorithm reduces the cost of adult fracture clinic visits by up to £104,800 per year: a quality improvement study

Abstract: Derby Teaching Hospitals NHS Foundation Trust, UKABSTRACT INTRODUCTION Inappropriate referrals to the new patient fracture clinic unnecessarily consume hospital resources and many hospitals lack clear guidelines as to what should be referred. Many of these injuries can be definitively managed by the emergency department. Our aim was to construct and disseminate a clinical decision-making algorithm to reduce the frequency of inappropriate referrals to fracture clinics at our institution, to improve the manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The VFC depends on collaboration with the ED for protocoldriven and leaflet-supported direct discharge of suitable injuries. Patients are also encouraged and empowered to take responsibility for the care of their nonsignificant injury, with virtual care leaflets containing information on rehabilitation and what to do if issues arise [3,[6][7][8]. The ED and neighbouring minor injury units (MIUs) at our institution refer fracture clinic patients to the VFC.…”
Section: Introductionmentioning
confidence: 99%
“…The VFC depends on collaboration with the ED for protocoldriven and leaflet-supported direct discharge of suitable injuries. Patients are also encouraged and empowered to take responsibility for the care of their nonsignificant injury, with virtual care leaflets containing information on rehabilitation and what to do if issues arise [3,[6][7][8]. The ED and neighbouring minor injury units (MIUs) at our institution refer fracture clinic patients to the VFC.…”
Section: Introductionmentioning
confidence: 99%
“…A study published in 2017 showed that a referral algorithm, described as a ‘simple educational intervention’, can effectively reduce the burden of inappropriate referrals and improve service use and cost-efficiency. 24 Reflecting on hospital practice, this toolkit may reduce the number of patients with COVID-19 who are admitted to limited-capacity ICUs by following the patient allocation algorithm ( figure 1 ). Moreover, it has been demonstrated that an algorithm-guided, standardised approach to evaluating patients can save resources without sacrificing patient outcomes or diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown significant cost savings can be made through the use of virtual clinics [5] . In addition, the use of virtual clinics has been shown to significantly improve waiting times for first clinical review especially in foot and ankle fracture cases [6,7] . With the growing interest in the balance between developing safe and robust patient pathways whilst reducing costs, there is a balance to be struck between cost savings on the one hand and safe effective care on the other.…”
Section: Discussionmentioning
confidence: 99%